The influence of transformational leadership, job satisfaction, and organizational commitments on Organizational Citizenship Behavior (OCB) in the inspectorate general of the Ministry of Education and Culture - Siti Nurjanah; Vina Pebianti; Agung Wahyu Handaru (Cogent Business & Management, 2020)
This research aims to determine the influence of transformational leadership and job satisfaction on OCB with mediating organizational commitment variables from 196 Civil Servants at the Inspectorate General of the Ministry of Education and Culture, Jakarta, Indonesia. The data analysis method uses the Partial Least Square (PLS) method. The results of the study show that (1) transformational leadership has a significant and positive effect on organizational commitment, (2) job satisfaction has a significant and positive effect on organizational commitment, (3) organizational commitment has a significant and positive effect on OCB, (4) transformational leadership has a significant and positive effect on OCB, (5) job satisfaction has a significant and positive effect on OCB, (6) transformational leadership has a significant and positive effect on OCB through organizational commitment, and (7) job satisfaction has a significant and positive effect on OCB through organizational commitment.
Keywords: 650; transformational leadership; job satisfaction; Organizational Citizenship Behavior (OCB); organizational commitment